Film Dokumenter Makanan Tradisional Bika Nagari Koto Baru, Tanah Datar - Muhammad Razi; Defrizal Saputra (Jurnal Pendidikan Indonesia (JOUPI), 2024)
The making of this documentary aims to promote to the public about the traditional food bika koto baru found in Tanah Datar Regency. The promotion aims to increase the existence of traditional bika koto baru food in the midst of the existence of modern foods at this time. This documentary was made using the Capcut Pro 2023 application for video editing. The results of this study indicate that documentary films are effectively used as promotional materials for traditional bika koto baru food to the general public who have been set targets and assisted with supporting media as a promotional campaign for traditional bika koto baru food.